1998
DOI: 10.1038/sj.bmt.1701267
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell yields are frequently poor in patients with histologically indolent lymphomas especially when mobilized within 6 months of previous chemotherapy

Abstract: Summary:High-dose therapy with peripheral blood stem cell (PBSC) support is a frequently used treatment option in younger patients with poor prognosis histologically indolent (low-grade) non-Hodgkin's lymphoma (NHL), usually at the time of second or subsequent response to conventional-dose therapy. We have undertaken PBSC collection in 57 patients with histologically indolent NHL mobilized with either cyclophosphamide 1.5 g/m 2 or the ESHAP regimen, followed by daily G-CSF. Progenitor cell yields were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 17 publications
1
37
2
Order By: Relevance
“…They collected a median of 6.9 × 10 6 /kg CD34 ϩ cells/kg in a median of two leucaphereses with those patients mobilised in first remission, and those who had received less than six cycles of previous chemotherapy tended to have better results. In contrast, others have reported suboptimal PBSC harvest results in lowgrade NHL patients 27,33 with approximately 25% of patients failing to mobilise Ͼ1 × 10 6 /kg CD34 ϩ cells, using lowdose cyclophosphamide plus G-CSF. 33 For heavily pretreated patients with low-grade NHL we have obtained significantly improved results with the IVE regimen collecting a median of 7.36 × 10 6 /kg CD34 ϩ cells compared to 2.92 × 10 6 /kg for patients mobilised with intermediate-dose cyclophosphamide (McQuaker et al, in preparation).…”
Section: Pbsc Mobilisation Using Salvage Combination Chemotherapy Regmentioning
confidence: 95%
See 1 more Smart Citation
“…They collected a median of 6.9 × 10 6 /kg CD34 ϩ cells/kg in a median of two leucaphereses with those patients mobilised in first remission, and those who had received less than six cycles of previous chemotherapy tended to have better results. In contrast, others have reported suboptimal PBSC harvest results in lowgrade NHL patients 27,33 with approximately 25% of patients failing to mobilise Ͼ1 × 10 6 /kg CD34 ϩ cells, using lowdose cyclophosphamide plus G-CSF. 33 For heavily pretreated patients with low-grade NHL we have obtained significantly improved results with the IVE regimen collecting a median of 7.36 × 10 6 /kg CD34 ϩ cells compared to 2.92 × 10 6 /kg for patients mobilised with intermediate-dose cyclophosphamide (McQuaker et al, in preparation).…”
Section: Pbsc Mobilisation Using Salvage Combination Chemotherapy Regmentioning
confidence: 95%
“…In this context it is well recognised that previous chemotherapy and radiotherapy can adversely influence the yield of CD34 ϩ cells. [9][10][11]26 Also, there is evidence that patients with lowgrade lymphoma are more likely to be poor mobilisers, 27 such that the number of these cases in any series is likely to affect the overall results. It is possible, however, to make some general conclusions.…”
Section: Pbsc Mobilisation With Cyclophosphamide and Growth Factorsmentioning
confidence: 99%
“…Therefore in this larger study, we have been able to demonstrate that the improvement in CD34 ϩ cell yields achieved using G-IVE is attainable not just in patients who may be regarded as good mobilisers (ie high-grade NHL) but also in those patients with Hodgkin's disease and low-grade lymphoma who have previously been reported to be difficult to mobilise successfully. 17,21,22 In particular, Perry et al 21 have reported that mobilisation with cyclophosphamide (1.5 g/m 2 ) and G-CSF resulted in significantly lower progenitor cell yields in patients with low-grade lymphoma compared with patients with high-grade lymphoma and Hodgkin's disease. In their study, more than 20% of their patients with low-grade NHL failed to mobilise Ͼ1.0 ϫ 10 6 /kg CD34 ϩ cells, while 70% failed to mobilise Ͼ2.0 ϫ 10 6 /kg CD34 ϩ cells which they consider to be optimal for rapid engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 It is clear that previous chemotherapy and radiotherapy can impair the mobilisation of sufficient CD34 ϩ to proceed with transplantation. Furthermore, it has also been reported that in patients with previously treated low-grade lymphoma stem cell mobilisation often results in poor progenitor cell yields, 21,22 which may be a consequence of previous exposure to alkylating agents such as chlorambucil and purine analogues which are commonly used as initial treatment in these disorders.…”
mentioning
confidence: 99%
“…[23][24][25][26] Cytotoxic agents, with or without growth factor, are known to damage both hematopoietic and mesenchymal marrow stem cell compartments, thus suggesting that different chemotherapy agents might affect not only the quantity, but also the quality of mobilized progenitors. [27][28][29][30] No definitive assessment exists concerning the best chemotherapy mobilizing regimen given with G-CSF.…”
Section: Discussionmentioning
confidence: 99%